Pengaruh Penambahan Vitamin C Dosis Berbeda Terhadap Pertumbuhan Dan Kelangsungan Hidup Ikan Nila (Oreochromis niloticus) Betina - Sumaraw, Audi Yoel; Mulis; Ahmad, Indra G (Cenderawasih University, 2024)
Artifficial fee nutrition can be enhanched by adding vitamin C, aiming to suport the growth and survival of female Nile tilapia (Oreochromos niloticus). The addition of vitamin C to feed for the growht an d survival of fish has been extensively studied. However, there is still limited research specifically focusing on female Nile tilapia. The study aims to investigate the effect of vitamin C supplementation in feedd and to determine the optimal dosage for the growth and survival of fimale Nile tilapia juveniles. The research adopts an experimental approach using a Completely Randomized Design (CRD), consisting of 4 treatments and 3 replications. The treatments include A (Vitamin C 200 mg/kg feed), B (Vitamin C 300 mg/kg feed), C (Vitamin C 400 mg/kg feed) and D (Without vitamin C supplementation). Based on the results, the treatment with 300 mg/kg feed provide the best outcome, followed by treatment A and treatment C. The ANOVA analysis results indicate that there is no significant effect on growth (Fcount < Ftable) with a significance value >0.05, while there is a significant effect on survival (Fcount > Ftable) with a significance value < 0.05. Therefore, it is concluded that adding vitamin C to feed does not significantly affect the growth of female Nile tilapia juveniles but results in better growth compared to not providing vitamin C. In addition, of vitamin C significantly affects survival. Keywords: Female Nile Tilapia, Growth and Survival, Vitamin C